Synthesis and characterization of antimicrobial polylactide via ring-opening polymerization and click chemistry methods - Aynali, Figen; Doganci, Erdinc; Doruk, Tugrul; Sadikoglu, Hasan (WILEY, 2019)
Novel biodegradable polylactide (PLA) copolymers bearing pendant antimicrobial agent groups were successfully fabricated with a combination of ring-opening copolymerization and copper(I)-catalysed azide-alkyne cycloaddition click reaction in a two-step reaction procedure. First, biodegradable PLA copolymers bearing azido groups were synthesized by the ring-opening copolymerization of l-lactide and 2,2- bis(azidomethyl)trimethylene carbonate in the presence of 1-dodecanol as protic co-initiator and tin(II) 2-ethylhexanoate (Sn(Oct)(2)) as the catalyst. Then, alkyne functionalized quaternary ammonium salts were attached onto the azido groups of the copolymers via a Huisgen 1,3-dipolar cycloaddition reaction to give PLA imparting antimicrobial activity. The chemical structure and composition of the copolymers were clearly confirmed using H-1 NMR and Fourier transform infrared spectroscopies and gel permeation chromatography. Thermal phase transition temperatures (T-m and T-g) and the thermal stability of the polymers were investigated by DSC and TGA experiments, respectively. The antimicrobial activity tests were carried out against Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria by the drop plate method. It was observed that antimicrobial agents are more active in the polymeric form than in the monomeric form. Also, the activity depends on the compositional ratio and the length of the alkyl group on the ammonium salts. (c) 2018 Society of Chemical Industry
Keywords: polylactide copolymers; antimicrobial agents; click reaction; ring-opening copolymerization; ANTIBACTERIAL ACTIVITY; QUATERNARY AMMONIUM; POLYMERS; COPOLYMERS; POLYESTERS; Polymer Science